The Determinant Of Auditor Career Survivability Adopting The Blockchain Technology - Deny Nitalia Mindrawati; Grahita Chandrarin; Harianto Respati (Pusat Riset dan Inovasi Nasional, 2024)
This empirical study examined the influence of the auditor perspective on the supportive factors of blockchain technology adoption and the implication on auditory career survivability. The current research population consisted of all auditors in Indonesia, 6.034 individuals. The researchers used the Slovin formula to take 375 respondents. The researchers analyzed the obtained data with a validity test, reliability test, and path analysis. The results found the perception of the auditor about the positive and significant influencing factors toward the blockchain technology adoption and survivability of the auditor's career. Blockchain technology adoption could not moderate the survivability of an auditor's career. The current research novelty dealt with the examined variables, from the qualitative study. Then, the researchers developed the research into quantitative research to provide significant evidence.